Digital Competencies of Elementary School Teachers - Dragana Trninić (Seminar.net)
Digital competencies contribute to the development of other significant skills for the modern, digital age, such as communication, content creation and participation. To teachers' digital competencies can influence their abilities to integrate technology into the teaching process. This paper addresses the digital competencies of elementary school teachers in the Republic of Srpska (Bosnia and Herzegovina). The aim of the study is to highlight the necessity of continuous education of educators in the field of digital literacy, enabling them to transmit the necessary knowledge to students in an adequate and acceptable manner. The results of the survey conducted through the questionnaire method indicate insufficient level of digital competencies among elementary school teachers, their awareness of this issue and their desire for additional education. This study has shown that primary school teachers in the Republic of Srpska (BaH) have basic knowledge about media and information literacy (MIL), but that their digital skills are insufficiently developed.